Mental health challenges during COVID-19: perspectives from parents with children with neurodevelopmental disabilities. Issue 1 (31st December 2022) - Currie, Genevieve; Finlay, Brittany; Seth, Ashish; Roth, Christiane; Elsabbagh, Myada; Hudon, Anne; Hunt, Matthew; Jodoin, Sebastien; Lach, Lucyna; Lencucha, Raphael; Nicholas, David B.; Shakako, Keiko; et al.
ABSTRACT: Background: The global pandemic and subsequent denials, delays, and disruptions in essential daily activities created significant challenges for children with neurodevelopmental disorders (NDDs) and their parents. Public health restrictions during the COVID-19 pandemic limited access to supports and services required by children with NDDs to maintain their health and well-being. Objective: This study sought to understand the impacts of these public health measures and restrictions on mental health from the perspective of parents with children with NDDs to inform pathways for public health policies responsive to the needs of this population. Method: Interpretive descriptive design was used to guide data collection and data analysis. Forty caregivers were interviewed about their experience with pandemic restrictions. Findings: Generic policy measures contributed to many gaps in families' social support systems and contributed to mental health challenges for children and their parents. Four themes emerged: 1) lack of social networks and activities, 2) lack of access to health and social supports, 3) tension in the family unit, and 4) impact on mental health for children and their parents. Recommendations: Emergency preparedness planning requires a disability inclusive approach allocating resources for family supports in the home and community. Families identified supports to minimize further pandemic disruptions and enhance recovery.